Publisher Correction: PP2A inhibition from LB100 therapy enhances daunorubicin cytotoxicity in secondary acute myeloid leukemia via miR-181b-1 upregulation. Issue 1 (December 2017) - Hu, Chao; Yu, Mengxia; Ren, Yanling; Li, Kongfei; Maggio, Dominic; Mei, Chen; Ye, Li; Wei, Juying; Jin, Jie; Zhuang, Zhengping; Tong, Hongyan
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.